Techniques for Improving Credit Risk Management in Commercial Banks (Global Scientific Review, 2022)
The main idea of the article is to recognize, reduce, prevent and improve credit/debit risks allocated by commercial banks to their customers, individuals and businesses. There are many types of risks facing banks and the most common of them is credit risk. Commercial banks study the financial situation of their customers by analyzing their place in society, but still expected and unexpectedly the financial situation of their customers becomes difficult, even aggravated. The article deals with forecasting, scoring, and working closely with the financial condition of banking clients, finding ways to repay their loans. One of these ways is to teach their clients the basics of entrepreneurship and business and how to apply them in practice before lending.